Revolusi AI: Bagaimana kecerdasan buatan mengubah kehidupan sehari-hari - Darmayanti, Silvi Nur Afifa (Maliki Interdisciplinary Journal, 2024)
The artificial intelligence (AI) revolution has become a driving force for significant change in various aspects of our lives. This article examines the impact of AI on key sectors such as health, education, business, entertainment, transportation, manufacturing, agriculture, and the environment. In healthcare, AI accelerates diagnosis and personalizes treatment. In education, AI provides adaptive learning experiences. The business and economic world uses AI for data analysis and automation, while the entertainment industry benefits from more personalized content. Autonomous vehicles and transportation optimization demonstrate the impact of AI in the transportation sector. In manufacturing, AI improves productivity and quality, while in agriculture, AI supports precision farming. This technology also plays an important role in environmental conservation. Despite its broad benefits, AI poses challenges such as data privacy, algorithm bias, and impact on jobs. This article advocates the need for clear regulations, education and training, multisectoral collaboration, inclusive AI development, oversight and accountability, and ongoing research and development to ensure that the AI revolution brings equitable and sustainable benefits to society.